Incorporating unnatural amino acids to engineer biocatalysts for industrial bioprocess applications. Issue 12 (24th September 2015) - Ravikumar, Yuvaraj; Nadarajan, Saravanan Prabhu; Hyeon Yoo, Tae; Lee, Chong‐Soon; Yun, Hyungdon
Abstract: The bioprocess engineering with biocatalysts broadly spans its development and actual application of enzymes in an industrial context. Recently, both the use of bioprocess engineering and the development and employment of enzyme engineering techniques have been increasing rapidly. Importantly, engineering techniques that incorporate unnatural amino acids (UAAs) in vivo has begun to produce enzymes with greater stability and altered catalytic properties. Despite the growth of this technique, its potential value in bioprocess applications remains to be fully exploited. In this review, we explore the methodologies involved in UAA incorporation as well as ways to synthesize these UAAs. In addition, we summarize recent efforts to increase the yield of UAA engineered proteins in Escherichia coli and also the application of this tool in enzyme engineering. Furthermore, this protein engineering tool based on the incorporation of UAA can be used to develop immobilized enzymes that are ideal for bioprocess applications. Considering the potential of this tool and by exploiting these engineered enzymes, we expect the field of bioprocess engineering to open up new opportunities for biocatalysis in the near future.